Are Malaysians Ready to Resume the New Norm? Findings From a Nationwide Study - Suet, Sherilyn Pak Cheng; Farrukh, Muhammad Junaid; Qi, Hee Mei; Saleem, Zikria; Salman, Muhammad; ur Rahman, Aziz; Goh, Khang Wen; Ming, Long Chiau (Frontiers in Public Health, 2022)
Objective: The study aimed to evaluate the knowledge, attitude, and practices towards prevention of COVID-19 among the general public in Malaysia. Methods: A cross-sectional study was conducted online among the general public in Malaysia from June 2020 to August 2020 between the second and third wave (Phase 3 of the Recovery Movement Control Order). Participants were conveniently recruited through multiple social media platforms to encourage nationwide participation. A patient-administered questionnaire was used to assess their knowledge, attitude and practice towards the prevention of COVID-19. For descriptive analysis, percentage, mean and standard deviation was used to report demographic characteristics and knowledge, attitude and practice scores. For inferential analysis, t-test, ANOVA, Pearson’s correlation, Spearman’s correlation, Chi-square test and Binary Logistic Regression was used to analyse the differentiation, association and correlations of the study variables. The confidence interval selected for this study was 95%. Results: A total of 420 respondents participated in this survey. The majority of the participants (n=412, 98%) were aware of COVID-19. Most participants (60%) learnt about the pandemic through social media. About half of the participants had poor knowledge (45.5%) and negative attitude (43.3%). Participants residing in urban areas showed good preventive practices as compared to those residing in rural areas (P<0.05). There was a significant association between participant’s attitude and preventive practices towards COVID-19, Where majority of the participants (57.4%) who showed negative attitudes were more likely to follow poor preventive practices. Conclusion: Despite having good knowledge, participants with a negative attitude towards COVID-19 were less likely to follow the preventive practices of COVID-19. People’s mindset and willingness may play an important role to influence their practices. Thus, these are the vulnerable groups, and strategies should be made to change their mindset through proper counseling and education.